Disparities in Supports for Student Wellness Promotion Efforts Among Secondary Schools in Minnesota. (February 2017) - Larson, Nicole; O'Connell, Michael; Davey, Cynthia S.; Caspi, Caitlin; Kubik, Martha Y.; Nanney, Marilyn S.
ABSTRACT: BACKGROUND: We examined whether there are differences in the presence of supports for student wellness promotion (1) between schools in city, suburban and rural locations and, (2) among rural schools, according to distance from a metropolitan center. METHODS: The analysis was conducted in a sample of 309 secondary schools using 2012 Minnesota School Health Profiles surveys and National Center for Educational Statistics Common Core Data. Scores for overall support addressed school health improvement coordination (range: 0‐29), collaboration on health education activities (range: 0‐5), and teachers' professional preparation (range: 0‐7). RESULTS: Mean overall scores for health improvement coordination (10.5 ± 7.3), collaboration on health education activities (3.0 ± 1.5) and professional preparation (4.0 ± 1.9) indicated supports are lacking in schools across city, suburban, and rural locations. Comparison of overall scores did not identify disparities; however, weaknesses and strengths of particular relevance for rural schools were identified in examining specific aspects of support. For example, the proportion of rural schools having a written school improvement plan was 54.8% compared to 84.6% of city schools and 64.3% of suburban schools (p = .01). CONCLUSIONS: Tailored training and technical assistance are needed to better support schools in implementing recommended wellness policies and practices.